Cooperation of Universities and Employers Aimed at High-Quality Training of Specialists in the Field of Culture: Experts’ View - V. V. Matveev; A. A. Annenkova; E. E. Semenova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with the acute problem of all times, i.e. employment of artistic university graduates. We mean employment in their specialty, obtained profession and gained skills and knowledge. The problem of graduates employment implies fear of employers to take inexperienced specialists and reluctance of education institutions to adapt curriculums to employers’ requirements and adjust education system to the current labour market. The Orlov State University of Culture provides an example of top management and staff work aimed at this problem solving that included serious and hard activity. The University fosters graduates’ adaptation on labour market, carries out necessary steps to promote the system ‘student – university – education institution – employer (customer)’ and develops partnership relations in order to shape common interests and understanding of the current situation.